Economic analysis of the feller buncher in Brazilian Eucalyptus plantations: modeling with time series - Munis, Rafaele Almeida [UNESP]; Camargo, Diego Aparecido [UNESP]; Rocha, Qüinny Soares [UNESP]; Pandolfo, Paloma Trevisan [UNESP]; da Silva, Richardson Barbosa Gomes [UNESP]; Simões, Danilo [UNESP] (Taylor & Francis, 2024)
In the context of increased demand for timber, forest managers must consider best practices in forest management and harvesting operations. Depending on the harvesting systems adopted, the uncertainties of the cost components may reflect the volatility of productivity and the expected value of the project. We investigated whether the uncertainties of the cost components have an influence on the productivity volatility and the expected value of the mechanized timber harvesting investment project with a feller buncher. Monthly feller buncher productivity volatilities were measured based on the absolute value of the percentage variation in the deviation of the cost and productivity components. We modeled productivity and cost components using geometric Brownian motion to estimate project value. Productivity showed a strong positive correlation with the cost components of economic depreciation, supervisor labor, fuel, and operator labor. Lubricating oil and economic depreciation were the most volatile cost components. Considering the deterministic economic analysis, the net present value was USD 3,849,619. When considering the probabilistic economic analysis, the average net present value was USD 187,319 ± USD 1,275,033. We verified that economic depreciation and fuel influenced feller buncher productivity. The uncertainties of these components affect the economic viability of the feller buncher in Eucalyptus plantations.
Keywords: Costs; forest operations; strategic decisions; timber harvesting; volatility